2018
DOI: 10.1002/adma.201800710
|View full text |Cite
|
Sign up to set email alerts
|

2D Perovskites with Short Interlayer Distance for High‐Performance Solar Cell Application

Abstract: 2D perovskites have emerged as one of the most promising photovoltaic materials owing to their excellent stability compared with their 3D counterparts. However, in typical 2D perovskites, the highly conductive inorganic layers are isolated by large organic cations leading to quantum confinement and thus inferior electrical conductivity across layers. To address this issue, the large organic cations are replaced with small propane-1,3-diammonium (PDA) cations to reduce distance between the inorganic perovskite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
255
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(272 citation statements)
references
References 29 publications
6
255
1
Order By: Relevance
“…This suggests that stronger interlayer interaction of thicker slices mitigates the quantum confine effect and/or the phase dispersity of (BDA)MA 3 Pb 4 I 13 ( n = 4) film is possibly suppressed, which will be further identified in the following. In the fabrication of solar cells, researchers add small amount of MACl and/or DMSO as additive to obtain highly oriented perovskite films and thus we also control the crystalline orientation and dispersity properties in this work . To simplify the notation, we denotes (BDA)MA 3 Pb 4 I 13 ( n = 4) film without additive as BDA‐control, (BDA)MA 3 Pb 4 I 13 ( n = 4) film with MACl and DMSO as BDA‐additive and (BA) 2 MA 3 Pb 4 I 13 ( n = 4) film without additive as BA‐control and (BA) 2 MA 3 Pb 4 I 13 ( n = 4) film with MACl and DMSO as BA‐additive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that stronger interlayer interaction of thicker slices mitigates the quantum confine effect and/or the phase dispersity of (BDA)MA 3 Pb 4 I 13 ( n = 4) film is possibly suppressed, which will be further identified in the following. In the fabrication of solar cells, researchers add small amount of MACl and/or DMSO as additive to obtain highly oriented perovskite films and thus we also control the crystalline orientation and dispersity properties in this work . To simplify the notation, we denotes (BDA)MA 3 Pb 4 I 13 ( n = 4) film without additive as BDA‐control, (BDA)MA 3 Pb 4 I 13 ( n = 4) film with MACl and DMSO as BDA‐additive and (BA) 2 MA 3 Pb 4 I 13 ( n = 4) film without additive as BA‐control and (BA) 2 MA 3 Pb 4 I 13 ( n = 4) film with MACl and DMSO as BA‐additive.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a novel type of 2D perovskite called the Dion–Jacobson (DJ) structure was fabricated into PSCs, reported by Mao et al, using LA n −1 M n X 3 n + 1 , with divalent amino L molecules They used divalent organic ligands; i.e., 3‐(aminomethyl)piperidinium (3AMP) and 4‐(aminomethyl)piperidinium (4AMP) as the spacer and the solar cell exhibited a fairly good efficiency of 7.32%. Later on, Ma et alreport a 13% efficiency using 1,3‐diaminopropane as spacer with methylammonium chloride (MACl), dimethyl sulfoxide (DMSO) as additive. After that, Ahmad et al reported a highly efficient 13.3% DJ phase PSCs with thousand hours ultrahigh stability using the same molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Through simple solution processing, perovskite dimensionality could easily be confined: 3D to quasi‐2D to 2D by tuning the percentage of long organic cation composition. Quasi‐2D has the generic chemical formula of (RNH 3 ) 2 (A) n‐1 M n X 3n+1 where n is an integer and RNH 3 is a primary aliphatic or aromatic alkylammonium cation acting as a spacer between the perovskite layers, A, M, and X are monovalent organic cation, metal cations, and halide anions, together forming the perovskite framework . With high desorption energy of long organic chain, the moisture stability of quasi‐2D (low n values) is far above that of 3D perovskite .…”
Section: Introductionmentioning
confidence: 99%
“…In the field, the ultimate goal is to have stable, highly efficient, large‐scale, inexpensive, and low‐toxicity lead‐free photovoltaics operating for longer lifetimes, to realize their future commercialization . To incorporate additional organic cations such as the 2‐phenylethylammonium cation (PEA + , C 6 H 5 (CH 2 ) 2 NH 3 + ), phenylmethylammonium (PMA + ) and n‐butyl‐ammonium (BA + ) cations with hydrophobic ligands forming 2D OIHP structures seem to be a unique way to inhibit moisture and oxygen damage . In addition, layered 2D perovskite structures are able to sustain structural stability even in nonambient conditions at higher pressures and lower temperatures .…”
Section: Introductionmentioning
confidence: 99%